Analisis Perhitungan Struktur Pembangunan Gedung Sekolah 4 Lantai di Semarang - Alim Muhroni; Tenardhy Aryarama Wijaya; Dirga Asmara Putra (Jurnal Teknik Indonesia, 2024)
To meet the community's educational needs, existing schools are encouraged to increase their student capacity by building new facilities. As public infrastructure, school buildings need to be designed as reliably as possible, including their earthquake resistance. To ensure that a building is earthquake-resistant, this study analyzes it using the ETABS software. This research was conducted in Semarang City on a four-story school building. The results indicate that the Participating Mass Ratio of the school building is greater than 90%. The comparison of the Response Spectrum with the Equivalent Static method shows 92.80% along the X-axis and 87.85% along the Y-axis. Based on the calculated inter-story drift, if an earthquake occurs with the provided data, the building is expected to withstand the event without collapsing.